The sustainable development of Jin opera costumes from the perspective of traditional cultural protection / Xing Furong, Azian Tahir and Syed Alwi Syed Abu Bakar. - Xing, Furong; Tahir, Azian; Syed Abu Bakar, Syed Alwi (Universiti Teknologi MARA, Perak, 2024)
Cultural heritage encompasses various forms, which includes tangible artifacts, intangible traditions, costume, and others. Indeed, the protection of cultural heritages plays a vital role in preserving and transmitting human culture. In this case study the Jin opera costumes are the most important to be studied due to its direct and graphic factor that actors use in their play roles. This paper uses the theory of heritage protection and sustainable development. First, the article summarizes the expression of Jin opera costumes. Secondly, the article further analyses the form of expression and concludes that the costume culture of Jin opera has the artistic beauty of colours. Finally, the article understands the development of Jin opera costume culture through analysis. On this basis, the paper integrates the concept of cultural protection to derive a sustainable development path to analyse the aesthetics of Jin opera costumes. At the government level, local governments should actively introduce heritage protection plans and systems. At the social level, all sectors of society need to fully consider personalized sensory enjoyment, effectively integrate traditional culture industry, and form a digital dissemination system of Jin opera costume cultural heritage with diversified content based on the support of digital technology. At the level of relevant institutions of Jin opera, they need to use digital technology to collect various data related to the Jin opera costumes and integrate and store costume data. By promoting the sustainable development of Jin opera costumes by building a complete costume cultural heritage database.